Integrating waqf via microfinance to alleviate poverty in Malaysia / Normilia Abd Wahid ... [et al.] - Abd Wahid, Normilia; Ramli, Noor Affeeda; Che Hamzah, Hamnah; Zainal, Nor Fadzilah (2012)
Waqf is known as philanthropic or endowed institution that has played a significant role throughout Islamic history beginning from the time of the Prophet Muhammad s. a.w until the end of Ottoman Empire in 19th century. As an Islamic endowment institution, waqf has successfully contributed in providing good public utilities, health care, education and other aspects of socio economic development of the ummah (Muslim society). However after the collapse of Ottoman Empire, waqf seems to losing its power io serve the ummah. In Malaysia the institution of waqf still plays its role even though it is not as prominent during the period of Ottoman Empire. Besides waqf, micro financing or micro credit also plays a Significant role in poverty alleviation programs. It is proven that micro credit is highly demanded and able to help "un banked" people to live Out of poverty. One such example can be found in the practice of Grameen Bank in Bangladesh which gives small credit to the poor to start a business. This study aims to integrate the waqf into micro finance in alleviating poverty in Malaysia and their challenges. Recommendations on modes of financing under the waqf based micro finance will be suggested at the end of study in order to improve the way it serves the ummah.